Cengiz ve Diğerleri / Türkiye Karar İncelemesi - Saygılar Kırıt, Yasemin F.; Gezer, Özge Sırma (Seçkin Yayıncılık, 2018)
Ankara Sulh Mahkemesi kararıyla Mayıs 2008’de YouTube internet sitesine erişimin engellenmesinin ardından başvurucular, sosyal medya kullanıcısı sıfatıyla Avrupa İnsan Hakları Mahkemesi’ne başvurarak Avrupa İnsan Hakları Sözleşmesi’nin 10. Maddesinde yer alan ifade Özgürlüğü haklarının ihlal edildiği iddiasında bulunmuşlardır.

On May 2008, the Ankara Criminal Court of First Instance made order for the blocking of access to website http://www.youtube.com. The applicants complained that the measure taken by domestic courts had prevented them from having access to YouTube. They submitted that the measure amounted to an infringement of their right to freedom to receive and impart information and ideas, guaranteed by Article 10of the Convention.
Keywords: İfade özgürlüğü; Sosyal Medya; İnternet erişimi engellemesi; AİHM; Freedom of Speech; Social Media; Blocking of Access; ECHR